PENGARUH KOMITMEN ORGANISASI, KEPUASAN DAN PENGHARGAAN TERHADAP KINERJA KARYAWAN (Studi Kasus Pada BPR. Gunung Ringgit, Malang) - Muhammad Rasyiid Aziiz; Muhammad Mansur; Muhammad Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTPerformance in the organization is the answer to the success or failure ofcorporate goals. The purpose of this study is to determine the extent of theinfluence of organizational commitment, satisfaction and appreciation ofemployee performance in Rural Bank Rakyat Ringgit Dinoyo, Malang. Thepurpose of this study is to determine whether there is influence of OrganizationalCommitment, Satisfaction and Appreciation on Employee Performance at PT.BPR Gunung Ringgit Malang.The result of research shows that the three variables of OrganizationalCommitment, Satisfaction and Reward have significant influence to dependentvariable that is Rredit Bank Rakyat Ringgit Dinoyo, Malang. The biggestsignificant impact on Employee Performance at PT. BPR Gunung Ringgit Malangis on Organizational Commitment variable with Regression coefficient of 0,469then followed by variable of appreciation with regression coefficient equal to0,380 next variable Satisfaction with regression coefficient equal to 0,097. Fromthe results of the analysis can be taken a conclusion that OrganizationalCommitment is the dominant factor that has the greatest influence on the level ofPerformance of Rural Bank employees Ringgit Dinoyo, Malang.Keywords: Organizational Commitment, Satisfaction, Employee Awards andPerformance.